A qualitative exploration of consumers’ views and experiences toward online pharmacies: Narrative from a developing country - Amal K. Suleiman; Abbas Albarq; Ateeq Ur Rehman (PLoS ONE, 2025)
Introduction The widespread adoption of the internet and online pharmacies has made accessing medications more convenient, especially with the growing use of smartphones in developing countries. While these new purchasing methods offer ease of access, they also raise concerns about the prevalence of counterfeit drugs. This study examines consumer experiences with online pharmacies, focusing on the factors that influence purchasing decisions and the concerns associated with buying medicines and supplements in the context of a developing country. Method An exploratory qualitative study was conducted in Islamabad/Rawalpindi (twin cities in Pakistan’s federal area) from June to October 2023. Four focus group discussions (FGDs) were conducted, with each lasting approximately 30–40 minutes. The participants were approached in person, and the purpose of the study was explained to them. The participants were recruited after written informed consent was obtained. Grounded theory was used as the guiding methodology to explore consumer behavior toward products obtained from online pharmacies. After the culmination of data collection, the audio recordings originating from the FGDs were transcribed. Since the FGDs were conducted in Urdu, the audio recording was transcribed in Urdu verbatim. Subsequently, the transcripts were translated into English by an independent researcher who was fluent in Urdu and English. To ensure the accuracy, comprehensiveness, and impartiality of the transcriptions, independent verification of the transcripts was conducted by a second independent researcher. Results A total of thirty-two participants took part in the focus group discussions. The FGDs identified three themes, namely: reasons for the purchase of online medicines/supplements, psychological factors involved in the purchase of online medications and supplements, and concerns regarding online purchase of medicine and supplements. The themes were further divided into twelve subthemes. Participants cited the ease of payment, ease and convenience, low cost, choice, accessibility, and discounts as reasons for favoring online purchase of medicines and health/food supplements. Doubts about the efficacy of the medicines, safety concerns, and uncertainty regarding storage conditions were the psychological factors that study participants mentioned. Personal information leakage and the influx of unwanted advertisements via email, which they attributed to inadequate online security measures, were the main concerns regarding online purchase of medicine and supplements. Conclusion This study offers new insights into consumer behaviors and concerns regarding online pharmacies in a developing country, adding to the limited literature on this topic. While online pharmacies offer convenience and can stimulate economic growth, the study emphasizes the need for stricter regulation to address consumer concerns and ensure safe and reliable purchasing experiences.